Mysticism and Spiritualism in the Contemporary Era: Fostering Mental Resilience Amid Modern Challenges - Panji Guniwa Aria Awangga; Muhtar Solihin; Cucu Setiawan; Muhlas Muhlas (UIN Sunan Gunung Djati Bandung, 2026)
This interdisciplinary study bridges psychology, neuroscience, and mystical theology to elucidate mysticism and spirituality's therapeutic role in mental health, particularly in cultivating resilience, emotional stability, and existential recovery. Through descriptive-qualitative analysis of empirical studies, classical theories, and sacred texts across traditions, it probes neurobiological underpinnings—such as Default Mode Network (DMN) dynamics in mystical states—and distinguishes these ethically/clinically from psychosis. Findings reveal that practices like meditation, kataphatic contemplation, and guided visualization modulate brain networks governing emotional regulation, empathy, moral cognition, and autobiographical memory. Framed within coherent ethical narratives, mystical experiences forge existential meaning, aiding adaptation to trauma, loss, and identity crises, thus transcending mere stress reduction toward transformative self-renewal. Yet integration into clinical practice demands navigating ethical complexities: scientific validation, religious bias risks, and safeguarding patient autonomy amid cultural diversity. This research proffers a holistic framework for spirituality in mental health care, urging epistemological openness, interfaith dialogue, and alignment with global models (e.g., US, UK, India, Canada). Ultimately, it posits existential insight and cultural humility as indispensable to contemporary psychological care.